Fungal Peritonitis: A Case Series Detailing Clinical Presentations, Diagnostic Challenges, and Management Strategies - Grynchuk, Fedir; Grynchuk, Andrii; Grynchuk Jr, Fedir (Futurity Medicine, 2025)
Aims: to present the features of fungal peritonitis. Methodology: The case series comprised three patients: a 52-year-old male with a post-splenectomy subdiaphragmatic abscess, a 64-year-old male with post-operative peritonitis following a perforated duodenal ulcer repair, a 68-year-old female with primary peritonitis. The clinical history, physical examination findings, laboratory and imaging results, surgical reports, and treatment outcomes are presented. Results: All patients exhibited comorbidities. Non-specific symptoms characterized clinical presentations. Imaging modalities were valuable diagnostic tools. Candida albicans was identified as the causative organism in all cases. Conclusion: Fungal peritonitis is a clinically challenging condition with non-specific clinical and laboratory manifestations.